2015
DOI: 10.1016/j.jcmg.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Remodeling, Myocardial Viability, and Survival in Ischemic LV Dysfunction After Surgical Revascularization

Abstract: Objectives The objectives of this study were to test the hypothesis that end-systolic volume (ESV), as a marker of severity of left ventricular (LV) remodeling, influences the relationship between myocardial viability and survival in patients with coronary artery disease and LV systolic dysfunction. Background Retrospective studies of ischemic LV dysfunction suggest that severity of LV remodeling determines whether myocardial viability predicts improved survival with surgical (CABG) compared to medical (MED)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 41 publications
0
37
0
13
Order By: Relevance
“…CMR may also be used for the assessment of myocardial ischaemia and viability in patients with HF and CAD (considered suitable for coronary revascularization). However, limited evidence from RCTs has failed to show that viability assessed by CMR or other means identified patients who obtained clinical benefit from revascularization …”
Section: Cardiac Imaging and Other Diagnostic Testsmentioning
confidence: 99%
“…CMR may also be used for the assessment of myocardial ischaemia and viability in patients with HF and CAD (considered suitable for coronary revascularization). However, limited evidence from RCTs has failed to show that viability assessed by CMR or other means identified patients who obtained clinical benefit from revascularization …”
Section: Cardiac Imaging and Other Diagnostic Testsmentioning
confidence: 99%
“…Ograniczona liczba dowodów z RCT nie pozwoliła jednak na udokumentowanie klinicznych korzyści z rewaskularyzacji u pacjentów, u których żywotność mięśnia sercowego została oceniona w CMR [105][106][107].…”
Section: Rezonans Magnetyczny Sercaunclassified
“…Bo now et al reported that absence of viability with LV remodeling (end-systolic volume index > 84 ml/m 2 ) predicts the highest mortality regardless of treatment. However, combination of viability and LV remodeling did not influence the effect of CABG relative to medical therapy in STICH cohort [30].…”
Section: Outcomes After Revascularization Associated With Viabilitymentioning
confidence: 75%